Posted by **Anonymous** on Wednesday, July 9, 2014 at 7:12pm.

Let H(x)=F(G(x)) and J(x)=F(x)/G(x).

Suppose

F(7)=4, F′(7)=−8

G(7)=3, G′(7)=−5

G(2)=7, G′(2)=−2

then

H′(2)=

J′(7)=

## Answer This Question

## Related Questions

- calculus - Consider the interval I=[6,7.6]. Break I into four subintervals of ...
- College Physics - Use the relativistic coordinate transformation (x, y, z, t) &#...
- PHY 2054 - Use the relativistic coordinate transformation (x, y, z, t) − (...
- physics - Consider the two observers O and O′ at the origins of the ...
- calculus (point me in the right direction please?) - f(x) and f′(x) are ...
- calculus - F.(0) (10 puntos posibles) C1 What is limh→0cos(π...
- calculus - f(x) and f′(x) are continuous, differentiable functions that ...
- Maths-Calculus - If f(2)=1 and f(2+h)=(h+1)3, compute f′(2). If f(−1...
- Math- Calc - Suppose f(5)=5, f′(5)=5, g(5)=8, g′(5)=−8, and H(...
- math - f(x) and f′(x) are continuous, differentiable functions that ...

More Related Questions